Conservation Agriculture: An Eco-Friendly System of Weed Management in Field Crops - Karki, Tika Bahadur; Shrestha, Jiban (International Journal of Environment, 2014)
Since the conservation agriculture (CA) is spreading across the globe, information on weed dynamics and their management under CA is needed. Here, an attempt has been made to summarize the recent research on weed dynamics and their management aspects in the CA systems. Changes in patterns of tillage, planting systems, and other management strategies can alter the soil environment and lead to shifts in weed populations. Weed patterns and populations are not always stable but vary with location, crop, and herbicides use. However, in many long-term conservation management studies, a general increase in perennial weeds and grass species has been observed. No tillage increased the weed population during first season and there after decreased. Residue has significantly reduced the number of weed species and population compared to conventional agriculture systems. The development of low-dose of non-selective pre and selective post emergence herbicides, and transgenic crops has greatly improved the feasibility of CA systems. DOI: http://dx.doi.org/10.3126/ije.v3i4.11733 International Journal of Environment Volume-3, Issue-4, Sep-Nov 2014 Page: 91-100